The Relationship Between Maternal Age and Parity and the Incidence of Hypertension in the Third Trimester of Pregnancy at the Maja Community Health Center in 2026 - Eva Fauziah; Nurul Hidayah; Een Haenilah (Riviera Publishing, 2026)
Hypertension in pregnancy remains a major global public health problem, contributing significantly to maternal and fetal morbidity and mortality. This condition is influenced by multiple risk factors, including maternal age and parity, which play an important role in determining pregnancy outcomes. The objective of this study was to analyze the relationship between maternal age and parity and the incidence of hypertension in third-trimester pregnancy at the Maja Community Health Center in 2026. This study used an observational analytic design with a cross-sectional approach. The population consisted of third-trimester pregnant women recorded at the Maja Community Health Center, with a total sampling technique. Data were collected from medical records and analyzed using univariate and bivariate analyses with the Chi-Square test and prevalence ratio (RP). The results showed that 10.7% of respondents experienced hypertension in pregnancy. There was a significant relationship between maternal age and hypertension (p = 0.030; RP = 3.146), indicating that women in high-risk age groups had a higher probability of developing hypertension. A significant relationship was also found between parity and hypertension (p = 0.038; RP = 2.759). In conclusion, both maternal age and parity are significant risk factors for hypertension in pregnancy. These findings highlight the importance of early detection and targeted maternal health interventions to reduce complications during pregnancy.